Plasma Cortisol and Thyroid Hormone Profile in Theileria equi Affected Horses - Vidhyalakshmi, T.M.; Raval, S.K.; Sarvaiya, N.P.; Patel, S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Equine theileriosis caused by Theileria equi is an endemic disease in most of the countries. The latently infected animals may exhibit low performance following physical, immunological or mental stress due to the flare-up of underlying parasitemia leading to clinical form of the disease. In the present study, 72 horses were screened for T. equi by using polymerase chain reaction based on equine merozoite antigen-5 and 6, which revealed 25 to be positive for theileriosis. Further study was conducted to assess the cortisol and thyroid hormone (T3 and T4) levels in healthy (n=47) and in T. equi infected (n=25) horses. In horses positive for T. equi, there was significant increase (p<0.05) in cortisol (42.80±0.69 vs. 24.44± 0.12 ng/ml) and T4 level (47.56±4.06 vs. 38.14±2.40 ng/ml) with significant reduction (p<0.01) in T3 level (0.44±0.13 vs. 1.20±0.19 ng/ml) when compared to the healthy group. This may be the first report revealing that theileriosis infected horses are under stress due to the involvement of endocrine system as well as metabolic pathways.